6 The Impact of the Introduction of an Integrated Heart Failure Service at Torbay District General Hospital. (3rd June 2016) - Southwell, Lucy; Chester, Tim; Keeling, Phil; Magkiosis, Efstathios; Hawley, Alasdair
Abstract : Purpose: Torbay Hospital is a medium sized District General Hospital (DGH) in the South West of England with a resident population approaching 300, 000. We have been involved in NICOR (National Institute for Cardiovascular Outcomes Research) since its inception and continue to supply annual data to the National Heart Failure Audit. In May 2013 we established an integrated heart failure service (IHFS) at our hospital and describe the effect of this on this service. Methods: The IHFS comprises two cardiologists with an interest in heart failure and five heart failure nurse specialists (HFN) who rotate between the hospital and community (two were already trained and worked in the community under primary care, three (2.4 WTE) were new appointments who all needed training in heart failure). The IHFS aims to identify patients early following their admission, has daily out-reach ward rounds, and weekly HF meetings. Results: The Table 1 below shows NICOR audit data before, in the first transition year and after the introduction of the IHFS. Conclusions: We have shown that with the appointment of an additional 2.4 WTE HFNs and some re-structuring of our cardiology services it is possible to improve the management of patients admitted with HF (improved coding, patient identification, increased use of disease modifying medications in HFREF and better outpatient follow up and support in the community). It is also encouraging to observe a reduction in re-admission rates and 30 day mortality. This is interesting in that we now code a significant number of additional patients with severe valvar heart disease as having HFPEF and these patients are at considerable risk of early readmission and death. Over the next year we plan to continue to develop the IHFS particularly with improved education and self-management of HFPEF patients, cardiac rehabilitation programmes, and validation of GP HF registers.